Bed Load Variability and Morphology of Gravel Bed Rivers Subject to Unsteady Flow: A Laboratory Investigation. Issue 2 (7th February 2018) - Redolfi, M.; Bertoldi, W.; Tubino, M.; Welber, M.
Abstract: Measurement and estimation of bed load transport in gravel bed rivers are highly affected by its temporal fluctuations. Such variability is primarily driven by the flow regime but is also associated with a variety of inherent channel processes, such as flow turbulence, grain entrainment, and bed forms migration. These internal and external controls often act at comparable time scales, and are therefore difficult to disentangle, thus hindering the study of bed load variability under unsteady flow regime. In this paper, we report on laboratory experiments performed in a large, mobile bed flume where typical hydromorphological conditions of gravel bed rivers were reproduced. Data from a large number of replicated runs, including triangular and square‐wave hydrographs, were used to build a statistically sound description of sediment transport processes. We found that the inherent variability of bed load flux strongly depends on the sampling interval, and it is significantly higher in complex, wandering or braided channels. This variability can be filtered out by computing the mean response over the experimental replicates, which allows us to highlight two distinctive phenomena: (i) an overshooting (undershooting) response of the mean bed load flux to a sudden increase (decrease) of discharge, and (ii) a clockwise hysteresis in the sediment rating curve. We then provide an interpretation of these findings through a conceptual mathematical model, showing how both phenomena are associated with a lagging morphological adaptation to unsteady flow. Overall, this work provides basic information for evaluating, monitoring, and managing gravel transport in morphologically active rivers. Key Points: Bed load transport exhibits an inherent variability that depends on discharge and bed morphology Adaptation of bed topography to unsteady flow produces hysteresis in the bed load rating curve The clockwise hysteresis depends on flood duration relative to the time scale of bed evolution